Analisis Peran Standar Nasional Pendidikan dalam Upaya Peningkatan Mutu Pembelajaran di Indonesia - Nurmayani; Inaya Harahap, Rahma Putri; Alasta Selian, Zahwa Az-Zahra; Fitria, Suci; Hutagaol, Okti Sheril Febriana; Manik, Rifaldo Chandra; Silalahi, Winda Permata Sari; Silalahi, Aristobulus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Education is a fundamental foundation for national development, making it essential to establish standards that ensure the quality of education is distributed evenly. This study aims to analyze the role of the National Education Standards (SNP) in improving the quality of learning in Indonesia, covering the basic concepts, the scope of the eight standards, their implementation in educational institutions, the challenges faced, and their contribution to students’ learning quality. The method used in this study is library research by reviewing various sources such as scientific journals, books, and government regulations. The data were analyzed using a qualitative descriptive approach through data reduction, data presentation, and conclusion drawing. The results of the study indicate that SNP serves as the main reference in organizing education in a systematic, directed, and sustainable manner. The implementation of SNP begins with school self-evaluation, followed by quality-based planning and the application of student-centered learning. However, its implementation still faces several challenges, such as limited facilities and infrastructure, uneven teacher competencies, and suboptimal school management. Despite these challenges, SNP has shown a positive impact on improving the quality of learning, teacher professionalism, and educational management. Therefore, collaboration among the government, schools, and the community is needed to optimize the implementation of SNP in order to achieve equitable and high-quality education across Indonesia.